Comparative Analysis of Data Mining in Criminal and Fraud Detection - Dwivedi, Ayushi; Singh, Chintan; Mishra, Amarnath; Mishra, Ved Prakash (International Journal of Psychosocial Rehabilitation, 2020)
This manuscript explains the concept of data mining and its application in cybercrimes. Cybercrimes are becoming very serious day by day due to large data sets are generated by organizations and lack of the awareness of the internet users. The application of data mining in cybercrime and framework of data mining for detection of financial fraud is explained. A comparative analysis on digital forensic tools and techniques are done with their benefits